(untitled) (World Science, 2020)
This publication demonstrates the ultrastructural changes of the submandibular salivary gland under the opioid effect at the 2nd week of the experimental research. After 14 days of experimental opioid effect, we found the destructive changes in the organelles of exocrinocytes of acinar cells, as well as dyscirculatory processes. Capillary lumen was enlarged, overflowing with red blood cells. In the endothelium of the capillaries also noted the expansion of the granular endoplasmic reticulum. Small vacuoles appeared in the cytoplasm of endothelial cells. Single mitochondria located in the area of the endothelial cytoplasmic organelles are swollen. Due to the development of perivascular edema, the underlying connective tissue substance around the capillaries was impregnated with electron-illuminated transudate masses.